TEACHING ENGLISH LANGUAGE TO PAKISTANI ESL STUDENTS THROUGH REALIA AT PRIMARY LEVEL - Dr. Ahsan Bashir, Maryam Aleem, M Asif Ikram Anjum, Shakeel Ahmed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study highlights the importance of Realia in the process of English language learning at primary level.Out of many languages spoken, English language holds the key position in the economic uplift of the developing country like Pakistan. The literature is replete with the notion that English is not taught as a language but as a subject in Pakistan. For securing the better academic output of the class, Pakistani English language teachers use different methodologies and realia is one of these where a teacher uses real items from real life situations for the better comprehension of the young students. These young students acquire the skills and information which enable them to perform better in daily life. The sample consisted of twenty class one students selected through systematic randomization where the students were taught through realia for a period of two weeks. The statistical analysis of the data collected through the pretest and posttest scores of the sample revealed statistically significant gain in the performance of the students.